2016
DOI: 10.2147/opth.s115660
|View full text |Cite
|
Sign up to set email alerts
|

Amaurosis fugax – delay between symptoms and surgery by specialty

Abstract: PurposeTo describe the time course of management of patients with amaurosis fugax and analyze differences in management by different specialties.MethodsPatients diagnosed with amaurosis fugax and subjected to carotid ultrasound in 2004–2010 at the Sahlgrenska University Hospital, Gothenburg, Sweden (n=302) were included in this retrospective cohort study, and data were collected from medical records.ResultsThe prevalence of significant carotid stenosis was 18.9%, and 14.2% were subjected to carotid endarterect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Patients with AF usually present to ophthalmologists with isolated visual symptoms. Most study patients (41%) came to the ophthalmologist because of symptoms of AF; this observation was similar to the results of a prior study [ 17 ]. Some patients had a concurrent history of hemispheric neurologic symptoms, which might be why these patients did not initially consult ophthalmologists.…”
Section: Discussionsupporting
confidence: 87%
“…Patients with AF usually present to ophthalmologists with isolated visual symptoms. Most study patients (41%) came to the ophthalmologist because of symptoms of AF; this observation was similar to the results of a prior study [ 17 ]. Some patients had a concurrent history of hemispheric neurologic symptoms, which might be why these patients did not initially consult ophthalmologists.…”
Section: Discussionsupporting
confidence: 87%
“…Amaurosis fugax describes monocular or binocular loss of vision, typically lasting from 4 to 60 minutes. 3,4 The etiology of this symptom generally is a manifestation of thromboembolic disease in which atherosclerotic debris originating in the carotid artery or the aortic arch temporarily disrupts blood flow in the branch or central retinal arteriolar network. In some cases, appreciating Hollenhorst plaques during the fundoscopic examination on a routine eye examination, even in asymptomatic individuals, reflects significant thromboembolic disease—and especially so if a carotid bruit is appreciated by auscultation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to optimising modifiable risk factors, a presentation with ischaemic visual loss should prompt a rigorous assessment for the aetiology of the event, as the underlying cause is strongly associated with the risk of subsequent stroke, with particularly high risk in patients with symptomatic carotid artery occlusion and cardiac emboli [15-17]. …”
Section: Discussionmentioning
confidence: 99%
“…This could be due to delayed presentation from a patient perspective; a recently published Swedish study showed that the median patient’s delay from symptom onset to first contact with a doctor was 1 day, with a subsequent 3 day delay from first contact to investigation with carotid ultrasound [17]. Another potential factor could be administrative, as the majority of patients were referred from Moorfields Eye Hospital with an average one-day delay; this is in contrast to a previous study that found no difference in delay from symptom onset to assessment with between hospital specialists [17]. …”
Section: Discussionmentioning
confidence: 99%